Determination of elastic and viscoplastic material properties obtained from indentation tests using a combined finite element analysis and optimization approach - Kang, JiJun; Becker, Adib A.; Sun, Wei (SAGE, 2015)
Conventional indentation tests do not provide an accurate estimation of viscoplastic material properties. In this work, a combined finite element analysis and optimization approach is developed for the determination of elastic–plastic and creep material properties using only a single indentation loading–unloading curve based on a two-layer viscoplasticity model. Utilizing the indentation loading–unloading curve obtained from a finite element-simulated experiment with a spherical and a conical indenter, a set of six key material properties (Young’s modulus, yield stress, work hardening exponent and three creep parameters) can be determined. Non-linear optimization algorithms are used with different sets of initial material properties, leading to good agreements with the numerically simulated target loading–unloading curves.